2017
DOI: 10.1038/s41598-017-17163-x
|View full text |Cite
|
Sign up to set email alerts
|

QSKL protects against myocardial apoptosis on heart failure via PI3K/Akt-p53 signaling pathway

Abstract: The ancient traditional Chinese medicine Qishenkeli (QSKL) is widely used in the treatment of heart failure (HF) in China. Previous studies have shown that QSKL has definite effects on HF. The purpose of this study is to identify the regulation of QSKL on apoptosis and clarify the underlying mechanism. An apoptosis model of H9C2 cells was induced by oxygen-glucose deprivation/recovery (OGD/R). An animal model of HF was induced by ligation of left anterior descending (LAD) coronary artery in rat. We found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…QSG has been demonstrated to improve myocardial energy metabolism by regulating FA and glucose metabolism in the rat model of HF induced by AMI in this study. In our previous studies, we have established stable injury models of cardiomyocytes and fibroblasts in vitro [15,43]. We will explore the regulatory mechanism of QSG on the energy metabolism of cardiomyocytes and myocardial fibroblasts, and endeavor to find out which compounds in QSG can regulate the targets of myocardial energy metabolism in the future study.…”
Section: Qsg Protected Mitochondrial Function In Hfmentioning
confidence: 99%
See 1 more Smart Citation
“…QSG has been demonstrated to improve myocardial energy metabolism by regulating FA and glucose metabolism in the rat model of HF induced by AMI in this study. In our previous studies, we have established stable injury models of cardiomyocytes and fibroblasts in vitro [15,43]. We will explore the regulatory mechanism of QSG on the energy metabolism of cardiomyocytes and myocardial fibroblasts, and endeavor to find out which compounds in QSG can regulate the targets of myocardial energy metabolism in the future study.…”
Section: Qsg Protected Mitochondrial Function In Hfmentioning
confidence: 99%
“…QSG is a frequently prescribed formula with impressive cardio-protective properties for many years in China [13]. Previous studies reported that QSG could improve microcirculation by exerting anti-inflammatory, anti-apoptosis and anti-fibrosis effects [14][15][16][17][18][19]. In our previous study, mRNA transcriptomic analysis was used to investigate the regulatory pathway of QSG on HF rat model [20].…”
Section: Introductionmentioning
confidence: 99%
“…22,23 In addition, previous studies showed that Lonicerae Japonicae Flos, which was used in traditional Chinese formula, had significant benefits in the treatment of heart failure in clinical as well as animal research. 24,25 The effects of Lonicerae Japonicae Flos may be associated with its major active ingredient chlorogenic acid (5-caffeoylquinic acid, CGA). Earlier studies indicated that CGA has anti-inflammatory, 26 anti-oxidant, 27 anti-apoptotic, 28 analgesic, 29 antihyperalgesic 30 and antidiabetic effects.…”
Section: Tnf-α-induced Myocyte Apoptosis Involves Complicatedmentioning
confidence: 99%
“…Qishen granules (QSG), composed of Radix Astragali, Radix Salvia Miltiorrhizae, Flos Lonicerae, Radix Scrophulariae, Radix Aconiti Lateralis Preparata, and Radix Glycyrrhizae (Table 1), are a famous formula with cardioprotective properties prescribed to HF for many years. e previous studies have demonstrated that QSG could inhibit myocardial inflammation injury, cardiomyocyte apoptosis, and myocardial fibrosis [18][19][20][21] while its underlying mechanism remains to be further defined. Transcriptomics is a potent tool that offers convenient and reliable access to changes in the expression of genes, which could shed light into multiplexed mechanisms of drugs [22].…”
Section: Introductionmentioning
confidence: 98%